2018
DOI: 10.3390/genes9080389
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Analyses Suggests that Burkholderia sensu lato Contains Two Additional Novel Genera (Mycetohabitans gen. nov., and Trinickia gen. nov.): Implications for the Evolution of Diazotrophy and Nodulation in the Burkholderiaceae

Abstract: Burkholderia sensu lato is a large and complex group, containing pathogenic, phytopathogenic, symbiotic and non-symbiotic strains from a very wide range of environmental (soil, water, plants, fungi) and clinical (animal, human) habitats. Its taxonomy has been evaluated several times through the analysis of 16S rRNA sequences, concantenated 4–7 housekeeping gene sequences, and lately by genome sequences. Currently, the division of this group into Burkholderia, Caballeronia, Paraburkholderia, and Robbsia is stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(169 citation statements)
references
References 75 publications
(114 reference statements)
6
163
0
Order By: Relevance
“…Our inferred species tree of BCC reconstructed by these markers provided us with an accurate phylogenetic relationship. Together with dDDH and ANI, two methods that are useful for species demarcation and are powerful in BCC species differentiation [1,64,65], we delineated BCC species as 36 clusters. The results showed that the 22 currently known species correspond to 22 of these clusters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our inferred species tree of BCC reconstructed by these markers provided us with an accurate phylogenetic relationship. Together with dDDH and ANI, two methods that are useful for species demarcation and are powerful in BCC species differentiation [1,64,65], we delineated BCC species as 36 clusters. The results showed that the 22 currently known species correspond to 22 of these clusters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, diverse bacterial-fungal symbioses have been described, with fungal hosts ranging from tree endophytes to human pathogens (Arora and Riyaz-Ul-Hassan, 2018). One such partnership is Mycetohabitans rhizoxinica (family Burkholderiaceae; formerly Burkholderia rhizoxinica (Estrada-de Los Santos et al, 2018)) and the mucoromycete Rhizopus microsporus. A rice pathogen and opportunistic human pathogen, R. microsporus can also be found as a free-living soil saprophyte and is used in soy fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the demonstrated importance of the T3SS in the Rhizopus-Mycetohabitans partnership, no T3 effector proteins from M. rhizoxinica or any other endohyphal bacterium have been characterized (Nazir et al, 2017). However, homologs of transcription activator-like (TAL) effectors from plant pathogenic bacteria were identified in the first sequenced M. rhizoxinica genome (Lackner et al, 2011b;de Lange et al, 2014b;Juillerat et al, 2014;Estrada-de Los Santos et al, 2018). TAL effectors are T3secreted, sequence-specific, DNA-binding proteins that act as transcription factors once inside plant cells, upregulating target genes.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of bacteria that fix nitrogen in root nodules of leguminous plants are members of the α-Proteobacteria, Rhizobium, Bradyrhizobium, Ensifer , Phyllobacterium , Mesorhizobium , Devosia , Azorhizobium , Allorhizobium (Hirsch 1992; Sawada et al 2003; Lafay and Burdon 2007) and also Microvirga (Ardley et al 2012). Among the β-Proteobacteria, members of the Burkholderiaceae , known as beta-rhizobia, also nodulate legumes (Bontemps et al 2010, Gyaneshwar et al 2011, Estrada de los Santos et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the NRE are not pathogenic, but some may be serious pathogens of animals or plants, e.g., Staphylococcus, Bordetella (Sturz et al 1997; Xu et al 2014) and species of Burkholderiaceae such as B. cepacia (Eberl and Vandamme 2016). In the last few years, many of the symbiotic Burkholderia species (Gyaneshwar et al 2011) have been placed into new genera, e.g., Paraburkholderia and Trinickia (Sawana et al 2014; Estrada de los Santos et al 2018).…”
Section: Introductionmentioning
confidence: 99%